Pemetaan Strategi Kebijakan Pendidikan dalam Mewujudkan Pemerataan Akses dan Mutu Pendidikan: Sebuah Scoping Review - Nursaptini Nursaptini; Entoh Tohani (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Educational equity in access and quality remains a strategic issue that has attracted the attention of governments and policymakers worldwide. Numerous studies have examined educational policies aimed at promoting educational equity; however, the existing findings remain fragmented and have yet to provide a comprehensive understanding of the strategies employed. This study aims to map educational policy strategies for improving equitable access to and quality of education, identify major research themes, analyze conceptual relationships among these themes, and explore their implications for the development of Social Studies Education. The study employed a scoping review method of articles indexed in Scopus. The selection process resulted in 18 articles that met the inclusion criteria. Data were analyzed through thematic synthesis and strengthened by bibliometric analysis using co-occurrence network and thematic map techniques. The findings reveal that educational policy strategies can be categorized into five major dimensions: expanding educational access, improving educational quality, digital transformation, educational governance reform, and inclusive education. The bibliometric analysis indicates that the themes of education, access, quality, equity, and policy constitute the main conceptual structure of the literature. The thematic map identifies education and access as motor themes, while reforms and policy function as basic themes. Themes related to educational systems, the public sector, and inclusivity remain classified as emerging themes. The findings suggest that the development of Social Studies Education requires the integration of educational policy, curriculum development, and educational resources to foster social literacy and critical thinking skills. This study concludes that achieving equitable access to and quality of education requires an integrated approach involving expanded access, enhanced learning quality, policy reform, digital transformation, and strengthened principles of inclusivity to promote an equitable, high-quality, and sustainable education system.